Relationship between hepatitis C and kidney stone in US females: Results from the National Health and Nutrition Examination Survey in 2007–2018 - Chen, Yang; Shen, Xudong; Liang, Hu; Li, Guoxiang; Han, Kexing; Liang, Chaozhao; Hao, Zongyao (Frontiers in Public Health, 2022)
Abstract Background: The main objective of this study is to explore the effects of hepatitis C (HCV) on the prevalence rate of kidney stones in US females. Method: Dates for HCV infection and kidney stone were collected from National Health and Nutrition Examination Survey (NHANES) database, a cross-sectional study. The analysis samples included adults aged≥20 years females from six consecutive cycles of the NHANES 2007–2018. The association of HCV infection and kidney stone was performed by using logistic regression models.Subgroup analyses were conducted to find sensitive crowds. Results: A total of 13262 participants were enrolled,including 201 infected with HCV.After adjustment for potential confounders, we revealed a positive relationship between HCV and kidney stones(OR=1.70,95%CI:1.13-2.56). The crowds had a statistically significant difference was characterized by other races(OR=8.17,95%CI:1.62-41.22) and BMI within 25-29.9 kg/m2(OR=2.45,95%CI:1.24-4.83). Conclusions: HCV infection may affect the incidence of urolithiasis in US females, even the causal relationship remains unclear, the relation deserve special attention. We considered such a study an ideal way to begin exploring effects of HCV on kidney stone.